STUDENTS' CREATIVE WORK WITH TITLES OF TEXTS AS THE COMPONENT OF TRAINING FOR THEIR PROFESSIONAL ACTIVITY UNDER CONDITIONS OF MOUNTAIN ENVIRONMENT - Oleh Komar (Vasyl Stefanyk Precarpathian National University, 2015)
The article presents the attempt to reveal peculiarities of organization of students' creative work with titles of texts as the important component of their training for professional activity under conditions of mountain environment. The author accentuates on important aspects of Ukrainian foreign languages education system development and remarks that pragmatic aspect of comprehension of authentic texts titles plays an important role in foreign languages teaching. The titles are analyzed through their semantic and pragmatic peculiarities. Specific examples are given in order to sustain the ideas presented in the article. Afterwards the author presents the approximate classification of various techniques of work with the titles of authentic texts which are particularly applicable in the schools of mountain regions. These techniques are presented and analyzed from the viewpoint of potential use of cultural and background information content of titles in the process of foreign languages teaching.